2022
DOI: 10.1186/s12879-022-07573-2
|View full text |Cite
|
Sign up to set email alerts
|

Femoral osteomyelitis caused by oral anaerobic bacteria with mixed bacteremia of Campylobacter rectus and Parvimonas micra in a chronic periodontitis patient: a case report

Abstract: Background Campylobacter rectus is a gram-negative rod, and Parvimonas micra is a gram-positive coccus, both of which are oral anaerobes that cause chronic periodontitis. Chronic periodontitis can cause bacteremia and systemic diseases, including osteomyelitis. Hematogenous osteomyelitis caused by anaerobic bacteria is uncommon, and to date, there have been no reports of mixed bacteremia with C. rectus and P. micra. Here, we report the first case of osteomyelitis of the femur caused by anaerobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Intra-abdominal sources have also been identified as a cause of this bacteremia [ 6 ]. Many prior case reports regarding P. micra bacteremia were in the setting of immunocompromised patients or in patients with numerous comorbidities [ 1 , 2 , 5 ]. Similarly, the patient in this report had several comorbidities that made him vulnerable to this opportunistic pathogen, including his advanced age and extensive history of cardiac disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intra-abdominal sources have also been identified as a cause of this bacteremia [ 6 ]. Many prior case reports regarding P. micra bacteremia were in the setting of immunocompromised patients or in patients with numerous comorbidities [ 1 , 2 , 5 ]. Similarly, the patient in this report had several comorbidities that made him vulnerable to this opportunistic pathogen, including his advanced age and extensive history of cardiac disease.…”
Section: Discussionmentioning
confidence: 99%
“…Reports of bacteremia in the setting of this microbe are uncommon. Few reports, however, have been published establishing an association between P. micra bacteremia and colonic carcinoma, pneumonia, empyema, and osteomyelitis [1][2][3][4][5]. This case report details the clinical course and management of a patient who had P. micra bacteremia in the setting of a hepatic abscess.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with chronic periodontitis have a high tendency to develop osteomyelitis 20 , 21 . The proposed etiology is the biofilm produced by oral anaerobes, which can even influence inflammation in distant bones, such as the femur, through the blood stream 22 . Moreover, periodontitis can induce pathological changes in tissues adjacent to the oral cavity, such as the upper jaws, with great ease, leading to chronic inflammation of the paranasal sinuses.…”
Section: Discussionmentioning
confidence: 99%
“…found that those aged 19–35 had the most gingivitis, while the elderly had the most periodontitis. [ 22 23 24 31 32 33 34 35 36 ] Periodontitis was more common among patients aged 18–30 years according to a study on the incidence of periodontal diseases among 18–30-year-old individuals. [ 11 ] Our findings corroborate those of the prior research.…”
Section: Discussionmentioning
confidence: 99%